Activation of Conjunctiva-Associated Lymphoid Tissue in Diabetic Patients. (7th February 2023) - Liu, Yuting; Wang, Jingrao; Jin, Xin; Wang, Yingbin; Shi, Yan; Zhang, Nan; Zhu, Rui; Dong, Yueyan; Zhang, Hong
ABSTRACT: Purpose: To evaluate changes in conjunctiva-associated lymphoid tissues (CALTs) in patients with type 2 diabetic mellitus (T2DM). Methods: Thirty-two patients with T2DM and 32 healthy volunteers underwent comprehensive examinations. In vivo confocal microscopy and Image J were used to observe and evaluate the patients' CALT-related parameters. Conjunctival impression cytology (CIC) samples of the tarsal conjunctiva were collected from the patients, and CD4+ and CD8+ cells were evaluated by immunofluorescence staining. Results: The diabetes group showed higher diffuse lymphocyte density( p < .001), follicular density( p < .001) and parafollicular lymphocyte density( p < .001). The percentages of CD4+ cells ( p < .001) and CD8+ cells ( p < .001) in the diabetes group were higher than those in the control group. CALT-related parameters of the diabetic patients with diabetic retinopathy showed higher degrees of activation than those of the diabetic patients without diabetic retinopathy. Conclusions: CALT activation is observed in patients with T2DM, and the activation is more obvious in patients with diabetic retinopathy. Trial registration number: Retrospectively registered, ChiCTR2100046030.